Benchmarking the scalability of MPI-based parallel solvers for fluid dynamics in low-budget cloud infrastructure - Pereira Filho, Vanderlei M.; Castro, Márcio (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2022)
This ongoing study presents an analysis of the scaling of MPI-enabled partial differential equations (PDE) systems solver implementations with public cloud infrastructure. Shallow-Water equations are used as case study for analysis. Results indicate that public cloud can be a cost-effective solution for highly coupled problems, given a certain problem size threshold and appropriate infrastructure configuration. However, adequate software tooling and models are required for estimating and dimensioning optimal clusters.